THE COMPARATIVE LAW ON THE CRIME OF SEXUAL VIOLENCE BETWEEN INDONESIA AND THE UNITED KINGDOM - Sahlepi, Muhammad Arif; Nurita, Cut (Jurnal Pembaharuan Hukum, 2023)
The sexual violence is often experienced by women although it does not rule out the possibility that men can also experience sexual harassment. Each country has different regulations from one another regarding the definition, regulation and punishment of the Crime of Sexual Violence, as well as Indonesia and the United Kingdom. The type of research used is normative legal research or juridical normative, namely legal research based on examining library materials or secondary data materials which include research on legal norms. The purpose of this research is to analyze the legal regulation of criminal acts of sexual violence in Indonesia and legal comparison of criminal acts of sexual violence between Indonesia and the UK. So far, cases of sexual violence that mostly occur against women and children, including boys, are often just drowned and difficult to reveal. When they enter the legal process, it is not necessarily going to provide justice to victims. There are things done in the UK that Indonesia can emulate. For example, the Reynhard case came to light because at the University of Manchester there is a telephone complaint service, which offers support for victims of sexual violence or for those affected.